EFFECT OF DIFFERENT SOURCES OF PLANT GROWTH REGULATOR ON THE INDUCTION AND DEVELOPMENT OF MANGOSTEEN SOMATIC EMBRYOS - Yosi Zendra Joni; Riry Prihatini; Darda Efendi; Ika Roostika (Indonesian Journal of Agricultural Science, 2016)
Somatic embryogenesis is a technique for regenerating embryos derived from somatic cells of various plant species. This technique along with the utilization of plant growth regulator (PGR) might benefit for mass propagation and improvement of plant species through biotechnological tools. The study aimed to determine the effect of different plant growth regu-lators, namely 6-benzyladenine (BA) and thidiazuron (TDZ) on the embryogenic callus induction as well as casein hydrolysate and malt extract on the somatic embryo development of mangosteen. The explants used were in vitro young stems of mangosteen clone Leuwiliang. This study consisted of two experiments, namely induction of embryogenic callus and formation of somatic embryo. The first experiment was arranged as factorial in a completely randomized design with BA (0 and 0.7 mg l-1) as the first factor and TDZ (0, 0.1, 0.5 and 1.0 mg l-1) as the second factor. The second experiment consisted of four treatments, i.e. casein hydrolysate and malt extract at the rate of 500 and 1,000 mg l-1. The results showed that the best medium for embryogenic callus induction was MS supplemented with 0.1 mg l-1 TDZ, which resulted semifriable calli. Casein hydrolysate and malt extract could not induce the formation of somatic embryos. After two times subcultures on the same MS medium supplemented with 0.5 mg l-1 TDZ and 0.7 mg l-1 BA, a total of 33.8 somatic embryos per explant was induced. The successful somatic embryogenesis would support mangosteen breeding and in vitro mass propagation program.